Gingival enlargement as an early diagnostic indicator in therapy-related acute myeloid leukemia: A rare case report and review of literature - Triveni M Gowda; Raison Thomas; Shruthi M Shanmukhappa; Garima Agarwal; Dhoom S Mehta (Wolters Kluwer Medknow Publications, 2013)
Treatment for Hodgkin's lymphoma (HL) has resulted in excellent survival rates but is associated with increased risks of secondary therapy-related acute myeloid leukemia (t-AML). Gingival enlargement associated with bleeding and ulceration is the most common rapidly appearing oral manifestations of leukemic involvement. An 8 months pregnant patient reported with generalized gingival enlargement, with localized cyanotic and necrotic papillary areas. Co-relating the hematological report with the oral lesions and her past medical history of HL, a diagnosis of t-AML secondary to treatment for HL was made by the oncologist. As oral lesions are one of the initial manifestations of acute leukemia, they may serve as a significant diagnostic indicator for the dental surgeons and their important role in diagnosing and treating such cases. Furthermore, this case report highlights the serious complication of t-AML subsequent to HL treatment and the important role that a general and oral health care professional may play in diagnosing and treating such cases.